Increasing Front Rolls Learning Outcomes Through the Use of Learning Assistance Media - Iqbal, Muhammad (Mathematics Education Study Program, 2022)
This research uses Classroom Action Research (CAR). The data sources in this study were all seventh-grade students of Cawang Baru Junior High School Jakarta for the 2019/2020 Academic Year. The subjects of this research were the seventh-grade students of SMP Cawang Baru Jakarta for the Academic Year 2019/2020 totaling 22 people, consisting of 12 male students and 10 female students. Data collection techniques are through tests and observations of the process of learning activities. The data analysis technique used in this research is descriptively based on qualitative analysis. The procedure of this research includes planning, acting, observing, and reflecting. The results of the study show that the learning outcomes of the VII students of SMP Cawang Baru Jakaeta for the Academic Year 2019/2020 can be improved through use of learning aid media. From the results of the analysis obtained, there is an increase in the learning outcomes of front roll from the initial conditions to cycle I and cycle II. The results of the front roll learning have initial conditions (36%), cycle I (60%), cycle II (70%) with 18 students who completed. The conclusion of this research is that the use of learning aids media can improve the learning outcomes of front roll in class VII students of SMP Cawang Baru Jakarta for the Academic Year 2019/2020.